Use of dietary supplements among male fitness club members in Nis, Serbia. (30th September 2020) - Ramic, M; Jovanovic, M; Nikolic, M; Ramic, M; Nikolic, K
Abstract: Background: Dietary supplements use continues to increase in many countries. They are often used without a full understanding of the potential benefits and risks associated with their use, and without consultation with a health care professional. This study aimed to explore health beliefs and patterns of dietary supplement usage among fitness club participants. Methods: This cross-sectional study was conducted in fitness clubs of the city of Nis, Serbia. Male adults, age 18-45 years, participated. Data from participants were collected through an original structured, self-administered questionnaire describes the prevalence and type of supplements used, the reasons for using and the information source. Results: The prevalence of dietary supplement intake among participants was 85.86%. Most participants were between the age of 20 and 40 years, had a college degree (57.1%), non-smokers (80.5%), without chronic disease (86%), perform exercise at least thrice weekly (76.2%) and 63% had at least1 hour. The percentage of participants who had favorable health views on dietary supplements was significantly higher among the supplement users than among the non-users (P < 0.0001). Most participants (76.19%) perform exercise from 3 to 5 times weekly and 82.85% had from 1 to 2 hours exercise duration. The percentage of subjects who think supplements have side effects was significantly higher among the supplement non-users than among the users (p < 0 .05). Proteins (83.33%), amino acids (63.09%) and creatine (52.38%) were the most commonly reported supplements used. The places of buying dietary supplements most mentioned were specialized supplement store (78.57%), online (11.9%) and pharmacy (9.52%). Conclusions: Male fitness club member are large consumers of dietary supplements. Public health campaigns could be useful to educate Serbian population regarding using dietary supplements during fitness activities. Key messages: Male fitness club members are large consumers of dietary supplements in Serbia. Public health campaigns are needed to educate fitness participants about using dietary supplements.